Moderating Effects of Hardiness and optimism on negative life events and coping self-efficacy in first-year undergraduate students - Abbasi, Mohammad; Ghadampour, Ezatollah; Hojati, Mohammad; Senobar, Abas (Anales de Psicología / Annals of Psychology, 2020)
Introduction. This study analyzes the role of Hardiness and optimism on negative life events and coping self-efficacy in 228 first-year undergraduate students from lorestan university (iran). The aim of the study was two-fold: (1) to analyze the associations between Hardiness, optimism, negative life events and coping self-efficacy; and (2) to determine whether Hardiness and optimism moderates the relationship between negative life events and coping self-efficacy. Method. This descriptive correlational study was conducted in the school year of 2016-17. In this study, at first we selected 228 students. Then the students completed the Adolescent Life Events Questionnaire (ALEQ), Revised Life Orientation Test (LOT-R), Kobasa's Hardiness Scale, and Coping Self-Efficacy Scale (CSE). Hierarchical linear regression analyses were used to examine the moderating role of Hardiness and optimism. Results. Results reveal that there is a significant Relationship between Hardiness, optimism, negative life events and coping self-efficacy. Hardiness and optimism was also a moderator in the relationship between negative life events and coping self-efficacy. Conclusion. The findings supported the hypothesis that higher levels of Hardiness and optimism would be associated with higher levels of Coping Self-Efficacy, and that lower levels of Hardiness and optimism would be associated with lower levels of Coping Self-Efficacy. Finally, our results imply that Hardiness and optimism is an important moderator of student’s negative life events on Coping Self-Efficacy.